The Folly of Forecasting: The Effects of a Disaggregated Demand Forecasting System on Forecast Error, Forecast Positive Bias, and Inventory Levels - Brüggen, Alexander; Grabner, Isabella; Sedatole, Karen L. (The Accounting Review, 2021)
ABSTRACT Periodic demand forecasts are the primary planning and coordination mechanism within organizations. Because most demand forecasts incorporate human judgment, they are subject to both unintentional error and intentional opportunistic bias. We examine whether a disaggregation of the forecast into various sources of demand reduces forecast error and bias. Using proprietary data from a manufacturing organization, we find that absolute demand forecast error declines following the implementation of a disaggregated forecast system. We also find a favorable effect of forecast disaggregation on finished goods inventory without a corresponding increase in costly production plan changes. We further document a decline in positive forecast bias, except for products whose production is limited owing to scarce production resources. This implies that disaggregation alone is not sufficient to overcome heightened incentives of self-interested sales managers to positively bias the forecast for the very products that an organization would like to avoid tying up in inventory. Data Availability: Data are the property of the research partner and may not be redistributed by the authors.